Етапи розроблення системи НАССР на молокопереробному підприємстві - Микийчук, М. М.; Остап’юк, С. Д. (Енергетика і автоматика, 2017)
THE DEVELOPMENT STAGES OF HACCP SYSTEM IN THE DAIRY PROCESSING ENTERPRISE M. M. Mykyjchuk¸S. D. Ostapyuk Product quality is one of the important industrial and economic indicators of work of agricultural enterprises. The problem that occurs every milk-processing enterprise, and which is all the more complicated is the effective marketing of dairy products, because the consumption of dairy products, and especially baby foods, ensuring high quality and competitiveness is of particular importance. That is HACCP – hazard analysis and critical control points – is a system of assessment and control of hazardous factors of food raw materials, technological processes and finished products, ensuring high quality and food safety. Nowadays, it is the actual model of quality management and food safety in the developed world. Important in this system is the fact that the application of its principles in greatly reduced levels of risks of hazards to life and health of consumers of food products. The purpose of research- is to develop methodological foundations for implementation of HACCP system , as a system of quality management in dairy enterprises. Materials and methods of research. Application of HACCP system in any food plant, the implementation of, and compliance with, procedures that ensure the implementation of the General principles of food hygiene. The General principles of food hygiene established by the international organization "The Codex Alimentarius Commission". It is based on the use of technical and scientific principles to the entire food production chain: from field (farm) to the table. To develop HACCP plans relative to the quality and safety of dairy products can be assigned to a separate specialized working groups. Upon completion of the HACCP plan are being developed for operators of the form and monitoring procedures, and corrective actions. It is necessary to conduct training production personnel who will be responsible for monitoring and documentation, and it is also helpful to develop a schedule of activities necessary for the initial implementation of a HACCP plan. The Codex Alimentarius structure of the implementation of HACCP in the form of 12 steps, of which 5 are preparatory, and 7 – the actual principles of the HACCP system. Results. The article presents the authors developed a complex phased development and implementation of HACCP system in the dairy processing enterprise. Using the "decision tree" has been set for critical control points at each stage of production: - CPC 1- " The process of milking cows "; - CPC 2- "Cooling and storage of milk "; - CPC-3- "Pasteurization of milk"; - CPC 4- " Cooling and storage of pasteurized milk." For each critical point has developed a monitoring system for carrying out planned procedures of observation and measurement, and the timely detection of violations of critical limits and corrective actions installed. All records and documents were signed by artists and included in the worksheets HACCP. After the introduction of the elements of the quality system based on the principles of HACCP increases the number of benefits and possible prospects for development of dairy enterprises. Conclusions In the milk processing plant was established critical control points and developed a monitoring system for carrying out the planned procedure observations and measurements, and timely detection of violations of critical limits. And set corrective actions when there is a violation of the critical limits at critical control points. It is planned to improve the application of the HACCP system, not only for dairy enterprises, but also for businesses that are directly involved in the production of raw materials.